Campaign Socialization Religious Freedom to Tolerance Religion of Student - Ilham Prisgunanto (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
This research talks about correlation between campaign socialization freedoms of religion in any mass media to religious tolerance student in campus. Theoretical studies in this research uses mass media effect communication mass media especially Uses and Gratifications theories. Data analysis is quantitative surveys for 100 students in campus. Finding research explains that in cognitive level just television give impact to understanding for student’s’ religious tolerance. Beside that in conative level impact for student’s religious tolerance come from poster media. This research explains that there are no correlation between socialization campaign and students’ religious tolerance.